Fabrication, characterization and performance analysis of sol–gel dip coated SnO2 thin film - Md. Nazmul Huda; Galib Hashmi (Discover Materials)
Abstract Transparent conducting oxide (TCO) is widely utilized in various fields of electronics and optoelectronics, including touch-screen technology, thin-film solar cells, dye-synthesized solar cells (DSSC), and more. Yet, the costs associated with TCO films can be substantial, for instance, roughly 40% of the total expenses of the dye-synthesized solar cells are due to the use of this component. Therefore, fabricating TCO using Tin oxide (SnO2) using the sol–gel dip coating method is the central theme of this study. Where emphasis has been given to attaining high performance using locally available low-cost materials in Bangladesh. Moreover, to find out the electrical and optical properties of the fabricated SnO2 thin film UV spectroscopy, energy dispersive spectroscopy (EDS), X-ray diffraction (XRD), four-point probe measurement, and thickness measurement have been done. In addition, uniformity and cracks in the crystals, and morphological images have been observed using scanning electron microscopy (SEM). A thin layer with a thickness of 144 nm and a resistivity of 2.27 Ω-cm has been created after 16 times dipping in sol–gel solution. The findings indicate that the thin films have an average transmittance of roughly 70% in the 300–1200 nm wavelength range. Furthermore, the outcome also reveals that the thin films’ average band gap is approximately 3.533 eV. The experimentally obtained data have been included in the simulation for performance analysis. As demonstrated by the simulation, by using this TCO, a maximum efficiency of 17.525% may be attained in a CdTe solar cell. If manufactured correctly, SnO2 TCO could potentially rival traditional FTO or ITO based TCOs in solar cell research.